Properties of a Composite Material with Mixed Imperfect Contact Conditions - de Castro, Luıs Filipe Pinheiro; Pesetskaya, Ekaterina (Mathematical Modelling and Analysis, 2016)
We present an analytical solution of a mixed boundary value problem for an unbounded 2D doubly periodic domain which is a model of a composite material with mixed imperfect interface conditions. We find the effective conductivity of the composite material with mixed imperfect interface conditions, and also give numerical analysis of several of their properties such as temperature and flux.